Perlindungan Hukum Istri dalam Hukum Keluarga Islam dalam Kasus Kekerasan dan Perselingkuhan dengan Perjanjian Pranikah - Firdaus, Firdaus; Mursal, Mursal; Desminar, Desminar; Rafifa, Farhani; Febrianti, Eti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines legal protection for wives under Islamic family law in Indonesia, particularly in cases involving domestic violence and infidelity, even when a prenuptial agreement has been in effect. A special case in Padang City attracted public attention because the husband violated the prenuptial agreement, which not only regulates the separation of assets but also contains clauses prohibiting violence and infidelity. The purpose of this study is to analyze the dynamics of the case from the perspective of positive Indonesian law, Islamic family law, and fiqh principles. This study uses a qualitative method with a juridical-sociological approach. Primary data was collected through interviews with the victim (RA, 32), the victim's lawyer, and judges from the Padang City Class 1A Religious Court. Secondary data were collected from legal texts, fiqh literature, and related academic studies. This analysis combines the Miles & Huberman model with the Robert E. Stake approach, including data collection, reduction, presentation, conclusion drawn, and direct interpretation. The findings of the study show that legal protection for victims is supported by various overlapping legal foundations, including the provisions of the Kompilasi Hukum Islam (KHI), the Civil Code, the Criminal Code, the Marriage Law, the Domestic Violence Law, and other related regulations. Fiqh principles such as al-umur bi maqashidiha (everything depends on intention) and ad-dharar yuzal (danger should be eliminated) also reinforce this protection. This study’s impact affirms multi-legal protection, encouraging wives to pursue justice confidently.